Gagasan Judicial Review dan Terbentuknya Mahkamah Konstitusi di Indonesia - Puguh Windrawan (UIN Sunan Kalijaga Yogyakarta, 2013)
The Constitutional Court plays a central role in the democratic systemgovernance. With a solid perspective of balancing state power, the court has been set upto interpret and review of conformity of every act and regulation. In Indonesia, aconstitutional court presence has an important meaning amid power shifting processes.As the supremacy to some extent moving away from the executive authority, theconstitutional court appears as the most prominence body instead of legislative board. Inaccordance with its duties and functions, the institution is able to give juridicalinterpretations to examine every regulation against The Constitution of The Republic ofIndonesia 1945.